Graph-powered recommendation engine in movie recommender system - Abdul Mutalib, Ratna Dewi; Hassan, Saadah; Chew, Yew Chong; Admodisastro, Novia Indriaty; Baharom, Salmi (Advanced Scientific Research, 2020)
Usually, people will search on the Internet for movie that they want to watch. However, it is tedious to find and choose movie that matched with their preferences due to a lot of information on the Internet. Therefore, most of the movie portals are adopting recommendation engine to filter and display user’s personalized content. In this paper, MyRecMovie is presented to recommend movies by using graph-powered recommendation engine. MyRecMovie adopts content based (CB) and collaborative filtering (CF) approaches with then further enhance the recommendations with graph-powered recommendation engine to provide movie recommendations to the user.